Enhanced Hydrogen Generation from Empty Fruit Bunches by Charcoal Addition into a Downdraft Gasifier. Issue 4 (10th March 2020) - Uddin Monir, Minhaj; Abd Aziz, Azrina; Vo, Dai-Viet N.; Khatun, Fatema
Abstract: Hydrogen production by co‐gasification of empty fruit bunches of palm oil could be enhanced by adding charcoal. Physiochemical characterization of raw feedstocks was performed to determine their exergy potentiality. The raw feedstocks, gasified charcoal, and the end product of produced gas were analyzed by different techniques. Gasification experiments were performed using a pilot‐scale downdraft gasifier. The heating value, composition of product gas, yield of hydrogen, and exergy efficiency were used to verify the improvement of hydrogen production during the co‐gasification process. Charcoal with empty fruit bunches of palm oil leads to a much higher yield of hydrogen than lower charcoal ratios or solely empty fruit bunches. This enhanced hydrogen fuel can contribute to future energy demand. Abstract : The bioenergy potentiality of mixtures of empty fruit bunches (EFBs) with varying percentages of charcoal was evaluated. Hydrogen generation through co‐gasification of EFBs could be significantly enhanced by adding charcoal. Carbon‐based nanoparticles were found to be responsible for bioenergy production. Heating value and hydrogen‐based exergy were increased by charcoal addition.